Gender Equality in Islam: Adi Hidayat’s YouTube Discourse - Yuliani, Yuliani; Wibawa, Darajat; Fakhruroji, M. (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study aims to describe the representation of women in Ustadz Adi Hidayat’s (UAH) sermons on YouTube, to analyze how such discourse is produced and reproduced within the socio-cultural context of Indonesia, and to identify its ideological implications for the understanding of gender equality in Islam. Employing Norman Fairclough’s Critical Discourse Analysis, the research explores three major themes: education and gender identity, women’s socio-economic roles, and historical figures as role models. The data were collected from UAH’s YouTube sermons, including both full-length lectures and viral short clips. The findings reveal that women’s representation is ambivalent: women are glorified, yet such glorification is bounded by normative constraints that tie them to domestic and spiritual roles. The discourse is produced within Indonesia’s patriarchal culture and reproduced through the algorithmic logic of social media that amplifies normative messages. Its ideological implication is the reinforcement of a new form of patriarchy termed affirmative patriarchy, a mechanism of control that works not through rejection, but through conditional recognition and symbolic praise. The main challenge of this research lies in its limited scope, focusing solely on UAH’s sermons, and in its methodological constraint of not examining audience reception. Practically, this study recommends promoting digital religious literacy and developing more egalitarian preaching strategies. This research proposes the concept of affirmative patriarchy, which extends the study of gender discourse in digital Islam and enriches critical discourse analysis within the field of religion and gender studies.